Pleomorphic liposarcoma of breast, presenting as a recurrent breast tumor - Durre Aden; Sufian Zaheer; Divita Saxena; Sunil Ranga (Wolters Kluwer Medknow Publications, 2022)
Primary pleomorphic liposarcoma of the breast is a very rare mesenchymal tumor. Sarcoma arising in the breast constitutes <1% of all malignant breast tumors, and liposarcoma of the breast has an incidence of 0.3% of all mammary sarcomas. It is a very aggressive tumor with a high incidence of recurrences and distant metastasis. They can mimic primary invasive breast cancer clinically as well as radiologically. Histology and radiological evaluation of the patient help correctly type and grade this malignancy. On microscopy, the tumor is composed of pleomorphic tumor cells with atypical lipoblast with areas of necrosis and mitosis. We report one such rare case here.